Occurrence of multi-antibiotic resistant bacteria isolated from food handlers' hands and utensils at different restaurants in Dhaka, Bangladesh - Sumi Akter; Ratna Akter; Md. Abdus Salam (Journal of Advanced Biotechnology and Experimental Therapeutics)
Restaurant customers consume food contaminated by germs, increasing the risk of foodborne disease. In this investigation, food handlers' hands and utensils from many restaurants near Sadarghat launch station in Dhaka, Bangladesh, were tested to determine bacterial contamination incidence. Standard procedures were followed in isolation and identification of bacterial isolates. Of the 60 analyzed swabs, 46.7% showed a positive culture for one or more potential bacterial contaminants. The occurrence of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Vibrio cholerae in the hands of food handlers was 50%, 33.4%, 33.4%, and 23.4%, respectively, and those in utensils was 33.4%, 16.7%, 16.7%, and 10%, respectively. The majority of tested isolates of P. aeruginosa (100%) showed the highest resistance phenomenon to ampicillin and tetracycline, V. cholerae (100%) to ampicillin, E. coli (80%) to ampicillin and streptomycin, and S. aureus (100%) to ciprofloxacin. All of the examined isolates of P. aeruginosa were found to be most sensitive to piperacillin-tazobactam, E. coli to imipenem and nitrofurantoin, S. aureus to gentamicin, amikacin, tetracycline and chloramphenicol, and V. cholerae to piperacillin-tazobactam, imipenem and amikacin. Remarkably, 100% of V. cholerae isolates were multidrug-resistant (MDR), with the highest multiple antibiotic resistance index (MARI) score of 0.428. Among the examined isolates, 75% of bacterial isolates showed MDR phenotype, while 90% of isolates recorded a MARI value greater than 0.2. Due to the increased risk of food contamination or cross-contamination from food handlers' hands and utensils, the findings of this study indicate that restaurant hygiene standards are inadequate and might have detrimental effects on the general public's health. Consequently, this highlighted the significance of further training to enhance food workers' understanding of proper hand-washing techniques. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 18-31]